The methodics of the teaching of russian in higher education - AMINOVNA, BARAKATOVA DILOROM (The journal of contemporary issues in business and government, 2021)
The methodology of the Russian language develops at the intersection of many sciences, and methodologists and teachers need to rely on their achievements. A teacher cannot but be simultaneously a psychologist, linguist, literary critic, didactic. The different and multifaceted analysis of the database on the grammar of Russian is analyzed based on the latest inquiries. The comparative insight on the Russian in higher educational institutions are proposed.